The real effect of innovation information disclosure: from the perspective of supplier innovation - Yonggen Luo; Xiaoli Feng; Jinyu Yang (China Journal of Accounting Studies, 2023)
ABSTRACTThis paper investigations the impact of customers’ innovation information discovery in management discussion and analysis (MD&A) on the innovation of suppliers. We find that the more innovation information disclosed in MD&A, the higher innovation level of the supplier, and the higher the similarity between the supplier’s patent and the customer’s patent. Further analysis shows that when the degree of information asymmetry between suppliers and customers is higher, innovation is more important to suppliers, suppliers are more dependent on customers, and customers discovery more forward-looking information, the role of customer innovation information discovery on supplier innovation investment is more obvious. The economic sequences test finds that the impact of customer innovation information discovery on supplier innovation significantly import the investment efficiency and enterprise value of enterprises. Our findings provide evidence on the influence of public textual information on the real economy from the perspective of supply chain and theoretical basis for the importance to intensify information discovery in the capital market.